Delineasi Kawasan Perencanaan, Studi Kasus: Rencana Detil Tata Ruang Geopark Ngarai Sianok Maninjau - Nasution, Anthony P.; Lestari, Forina; Karenina, Anna; ., Medtry; Haryonugroho, Budi (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2023)
The instigation of a Detailed Spatial Plan (RDTR) is currently the focus of both central and local governments in Indonesia. Delineation of a zone as the first step in formulating an RDTR requires a range of considerations, including physical and non-physical issues. This study aims to delineate a planning zone taking the Geopark Ngarai Sianok Maninjau as its case study. The data collection stage applies several methods, such as field observations, focus group discussions, interviews, and reviewing documents obtained from relevant local government offices. Data analysis is conducted by scaling method of several criteria, such as land use, tourism potential, geosite location, policy blueprints, etc. Upon applying these criteria, the study proposes Matur in the Agam Regency of the West Sumatra Province as the most appropriate zone to have its RDTR developed. This is one among four alternatives selected for this purpose. Ultimately, this study also identified several possible implications of the delineation process for developing a zone. Keywords: The Detailed Spatial Plan (RDTR); Geopark Ngarai Sianok Maninjau; delineation   Abstrak Penyusunan Rencana Detail Tata Ruang (RDTR) saat ini menjadi fokus kegiatan dari pemerintah pusat dan daerah di Indonesia. Penentuan delineasi kawasan perencanaan sebagai langkah awal dalam penyusunan RDTR membutuhkan berbagai pertimbangan, baik fisik maupun non fisik. Kajian ini bertujuan untuk merumuskan delineasi kawasan perencanaan dengan mengambil Kawasan Geopark Ngarai Sianok Maninjau sebagai studi kasusnya. Proses pengumpulan data menerapkan metode antara lain, observasi lapangan, focus group discussion , wawancara, serta review dokumen yang diperoleh dari beragam kantor pemerintah daerah. Analisis data mempergunakan metode pembobotan dengan beberapa kriteria seperti misalnya tata guna lahan, potensi wisata, lokasi geosite , arahan kebijakan dan lain-lain. Setelah mempertimbangan kriteria-kriteria ini, kajian ini mengajukan Matur di Kabupaten Agam, Provinsi Sumatera Barat sebagai zona yang paling tepat untuk dikembangkan sebagai kawasan yang akan disusun RDTR-nya. Kawasan merupakan salah satu dari empat alternatif lokasi yang dipilih untuk lokasi ini. Diakhir, kajian ini juga menghasilkan kemungkinan implikasi yang muncul dari kegiatan delineasi terhadap perkembangan kawasan. Kata kunci: Rencana Detail Tata Ruang (RDTR); Geopark Ngarai Sianok Maninjau; delineasi